Penguatan Pemahaman dan Pengamalan Keagamaan Anak melalui Optimalisasi Fungsi Langgar - Moch. Tohet; Fitria Nur Hayati (Intelektual: Jurnal Pendidikan dan Studi Keislaman, 2022)
The study aims to describe the eï¬€orts made by Langgar Nurul Istiqomah in maximizing the function of langgar as a means to instill and strengthen the understanding and practice of religious values. This type of research is qualitative and was carried out in the village of Randumerak, Paiton sub-district, Probolinggo district, East Java, precisely in the area of Langgar Nurul Istiqomah. Research data was obtained through the process of observation and in-depth interviews. The research data were analyzed using the Miles and Huberman technique. This study's results showed that the optimization of the breaking function was actualized with various activities every day. There are the study of the books of Safi>nat al-Naja>h, Hida>yat al-Shibya>n, and Taisi>r al-Khala>q; tahlil and marhabanan; tadarus Al-Qur'an; routine worship practices (rutinan); rewards and punishments. The diversity of these activities can ward oï¬€ the boredom of the students studying. This study suggests that learning houses such as langgar can improvise to liven up an active, intelligent, and fun learning atmosphere by holding various activities